An Overview of the Posttranslational Modifications and Related Molecular Mechanisms in Diabetic Nephropathy - Cao, Yu; Yang, Zhao; Chen, Ying; Jiang, Shuai; Wu, Zhen; Ding, Baoping; Yang, Yang; Jin, Zhenxiao; Tang, Haifeng (Frontiers in Cell and Developmental Biology, 2021)
Diabetic nephropathy (DN), a common diabetic microvascular complication, is characterized by its complex pathogenesis, higher risk of mortality, and the lack of effective diagnosis and treatment methods. Many studies focus on the diagnosis and treatment of diabetes mellitus (DM) and have reported that the pathophysiology of DN is very complex, involving many molecules and abnormal cellular activities. Given the respective pivotal roles of NF-κB, Nrf2, and TGF-β in inflammation, oxidative stress, and fibrosis during DN, we first review the effect of posttranslational modifications on these vital molecules in DN. Then, we describe the relationship between these molecules and related abnormal cellular activities in DN. Finally, we discuss some potential directions for DN treatment and diagnosis. The information reviewed here may be significant in the design of further studies to identify valuable therapeutic targets for DN.